(12x-3)=(7x-2)

Simple and best practice solution for (12x-3)=(7x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12x-3)=(7x-2) equation:



(12x-3)=(7x-2)
We move all terms to the left:
(12x-3)-((7x-2))=0
We get rid of parentheses
12x-((7x-2))-3=0
We calculate terms in parentheses: -((7x-2)), so:
(7x-2)
We get rid of parentheses
7x-2
Back to the equation:
-(7x-2)
We get rid of parentheses
12x-7x+2-3=0
We add all the numbers together, and all the variables
5x-1=0
We move all terms containing x to the left, all other terms to the right
5x=1
x=1/5
x=1/5

See similar equations:

| 2x-4/2=4x-5 | | d/20+1,140+d/12=1,320 | | 13=2(p−5)+9 | | 16=(5-c)4 | | 783=27j | | g(4)=19 | | 3x^2-√3x=0 | | 5(x+1)-4(x+1)=60 | | 56+2x=6x | | 7x-7=3x-36 | | (x-6)/2=-1 | | 5g=508g | | 1.86^2-16x=0 | | 120+.5x=40+.9x | | 2x+3+3x+4=37 | | -11t-12=3-10t | | -2(4t-5)+5t=6t-3 | | -19+3y-1=8y+15 | | -2x+26÷3=26 | | 11x+9=11x+9=6x−16x−1 | | -14g=12-13g | | -2x÷3+26÷3=26 | | 7.5-4n=14+7n | | 2(3x+4)+4x=13| | | 1+y/9=4 | | -10g+2=-1-9g-6 | | 19y+26=159 | | (4x+38)=360 | | 7-x=3x+2 | | 8×^2+4y+9=29 | | 1-5-5c=2c+10 | | x/4-6/4=-1 |

Equations solver categories